Earl Warren, Ernesto Miranda and terrorism - Guiora, Amos N. (Twelve Tables Press, 2018)
"Would Chief Justice Earl Warren apply Miranda v. Arizona to terrorists today? This is not a biography of Warren; that task has been admirably accomplished by others. In inquiring whether Warren would apply Miranda to terrorism requires that we travel back in time to answer the question posed. The fact that President Obama and Attorney General Holder could not agree highlights the complexity and controversy of the issue. The question is brought to the fore after every act of terrorism committed by an American on U.S. soil." --